Application of LGBT-themed Socios Scientific Issue Reference Books to Improve Students Knowledge in Senior High Schools - Meilianti, Dasni Elsa; Yustina, Yustina; Suwondo, Suwondo (Journal of Educational Sciences, 2021)
This study aims to determine the increase in students' knowledge through the application of reference books based on socio-scientific issues with the theme of LGBT (Lesbi, Gay, Bisexual, and Transgender) which have been developed previously and integrated into the reproductive system material in class XI humans. The research was conducted at SMA PGRI Pekanbaru. The method used in this research was a Research and Development. Sources of research data came from 50 Class XI MIPA students. Research design was One group pretest posttest only. Data collection obtained from the pretest and posttest results of students' knowledge. The results showed that the students' knowledge had increased in the posttest results from 52.8 to 86.7 with a relatively high increase (N-Gain 0.71). From the results of the study, it can be concluded that reference books based on socio-scientific issues with the LGBT theme can be used as additional biology learning media in high school on reproductive system material.